KESETARAAN GENDER DI PERGURUAN TINGGI: MASIHKAH SEBATAS KONSEP? - Helaluddin Helaluddin; Alamsyah Alamsyah; Duwi Purwati (Raheema, 2022)
Implementation of the issue of gender equality in the higher education system is still become an interesting discourse to date. Higher education is considered to bey a key institution in promoting gender equality in society. This study is a Systematic Literature Review (SLR) which aims to describe the issues of gender equality in universities throughout the world in the period 2011 to 2020. There are four stages used in this study, those are indentification, screening, eligibility, and inclusion. Furthermore, data obtained from these stages are analyzed using content analysis techniques. The results of the analysis show that despite various laws and regulations regarding gender mainstreaming in college, in their implementation there are still many gender inequalities in various colleges.